Utilization of Rubber seed shell and Palm Oil Fronds as Composite Materials for Automotive Industry - Rahmadini Syafri; Chairil Chairil; Muhammad Rizqi Pratama; Muhammad Alfayed; Kardina Febriani; Hardi Rahayu Saputra (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Rubber seed shell (RSS) and Palm Oil Fronds (POF) are types of solid waste produced from rubber and palm oil plantation that has not been fully utilized. Meanwhile, in the automotive industry, composites have been the material of choice in some of its components. For example, composite body panels have been widely used in sports cars and passenger cars. This study aimed to utilize RSS powder and POF fiber waste as reinforcing fillers for the composite matrix. The matrix used was liquid polyester resin with the addition of catalyst as a hardener. RSS, which has been carbonized, was then activated using H2SO4 while POF fiber was pre-treated with 5% NaOH, then characterized both fillers by FTIR and SEM. Composites filled by RSS and POF in 4 variations were tested for mechanical properties with matrix composites without fillers as controls. FTIR testing of RSS carbonized powder found that carbonyl group consisting of tar compounds and remnants of carbon dioxide compounds that lost after activation with the H2SO4 solution. Meanwhile in POF fibers found that carbonyl group consisted of lignin and hemicellulose disappear after pre-treatment by 5% NaOH. SEM testing of RSS and POF fillers showed changes in surface morphology. The RSS and POF surface became coarser and porous, and the fibrils of POF fiber more obvious. The mechanical properties showed that the optimum result obtained in the composition of Matrix/POF/RSS (92.5/2.5/5).